Dimensional optimization of variable thickness tube in T-shaped tube hydroforming using response surface methodology. Issue 1 (1st December 2022) - Chen, M T; Xiao, X T; Tong, J H; Guo, H; Zhou, F Q; Zhou, F
Abstract : In this work, a variable thickness tube blank geometry is proposed to be used in T-shaped tube hydroforming. The dimensions of the tube blank are optimized by the response surface method (RSM) linked with finite element simulation during T-shaped tube hydroforming. The influence of the wall thickness, angle and length of the tube blank are discussed on the thinning ratio and branch height. Multi-objective functions that relate objectives and design variables are formulated. Furthermore, the design variables having greatest impact on the objectives are obtained by sensitivity analysis. The optimal the geometric dimensions are determined within the given criterion by RSW and desirability approach. The optimized results have good agreement with the obtained results by finite element simulation and experiment.